Destination food image, satisfaction and outcomes in a border context: tourists vs excursionists. Issue 5 (25th April 2019) - Toudert, Djamel; Bringas-Rábago, Nora L.
Abstract : Purpose: The purpose of this paper is to examine the impact of cognitive destination food image in food expectation, satisfaction and visit outcomes within a local context of the USA–Mexico border. The differences between tourists and excursionists were also assessed for their possible implications in strengthening an active market strategy in the framework of the same objective. Design/methodology/approach: Four hypotheses were examined through Squares SEM techniques. The model validation was carried out assessing the measurement and structural model. Additionally a multi-group analysis was performed to test the tourists and excursionists moderation effect. The study used 518 questionnaires completed by US visitors in three important gastronomic regions of the coast of Baja California, Mexico. Findings: The results suggest that tourists and excursionists obey different dimensions when structuring cognitive destination food image which showed a significant impact on visitor satisfaction and future intentions. Originality/value: The moderation function of tourists and excursionists in the causal relationships of the research model was analyzed as one of the first explorations in food tourism marketing. In conjunction with other findings, this paper offers specific theoretical and practical implications on how to stimulate gastronomic consumption in these two segments of visitors.